The second mesiobuccal canal in three-rooted maxillary first molar of Karnataka Indian sub-populations: A cone-beam computed tomography study - Radhika Kewalramani, MDS, BDS; Chethana S. Murthy, MDS, BDS; Ravi Gupta, MDS, BDS (Elsevier, 2019)
Introduction: Elusive second mesiobuccal canal (MB2) in maxillary first molar are often missed during endodontic therapy and are a major cause of treatment failures. Its prevalence is known to vary among different populations and there is limited information on its prevalence in Indian population. Aim: This study investigated the prevalence and location of second mesiobuccal (MB2) canal in mesiobuccal root of maxillary first molar using cone beam computed tomography (CBCT) images in an Indian population. Materials and methods: CBCT images of 598 three rooted maxillary first molars were studied. In each CBCT image, the floor of pulp chamber was located and advanced by 2 mm to standardize the observation for MB2 canal. Its location was determined in relation to mesiobuccal (MB1) and palatal (P) canal. Statistical analysis: The data was analysed using descriptive statistics. The presence of MB2 canal was correlated with age, gender and tooth position using Chi square test. Results: The prevalence of MB2 canal in three rooted maxillary first molar was 61.9%. It was seen that the prevalence of MB2 was highest in 20-40years age group (67.4%) followed by > 40 years (57.5%) and lowest in <20 years (50.6%) and the difference was statistically significant (p = 0.005). It is located mesiopalatally; 2.5 mm ± 0.6 mm palatally and 1.0 ± 0.4mmmesially to the MB1 canal or present directly on the line joining the MB1 and palatal canal. Conclusion: There is a high probability of finding MB2 canal in Indian patients. The access cavity must be modified from a triangular shape to rhomboid shape. Troughingmesiopaltally (about 2.5 mm palatally and 1 mm mesially) from MB1 to a depth of about 2 mm from the floor of pulp chamber may be necessary for locating MB2 canal.